2019
DOI: 10.20396/rbi.v18i2.8652176
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of innovative social entrepreneurship

Abstract: Innovative social entrepreneurship (ISE) is a topic of recent interest in research. The knowledge of the determinants of ISE and the characteristics of the innovations created by them is still limited. Therefore, the present document aims to contribute to this knowledge; specifically, it explores the determinants of the innovative behavior of ISE, during its process of creation and growth, and discusses the nature of such innovations (type, novelty, scope and impact) created throughout that process. Based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…However, regarding social ecosystem dynamism, the results are significantly better in HV regions (z = −2.064, p = 0.039). This result is inconsistent with previous studies [86,93], which suggest that the level of support for social entrepreneurship in LV regions is perceived as more favorable than that in HV regions. In Mexico, Saiz-Álvarez and Rodríguez-Aceves [84] found intense cooperation that promotes a dynamic social ecosystem between universities, public administrations, social enterprises, and NGOs.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, regarding social ecosystem dynamism, the results are significantly better in HV regions (z = −2.064, p = 0.039). This result is inconsistent with previous studies [86,93], which suggest that the level of support for social entrepreneurship in LV regions is perceived as more favorable than that in HV regions. In Mexico, Saiz-Álvarez and Rodríguez-Aceves [84] found intense cooperation that promotes a dynamic social ecosystem between universities, public administrations, social enterprises, and NGOs.…”
Section: Resultscontrasting
confidence: 99%
“…However, Villegas-Mateos and Vázquez-Maguirre [16] found that the interactions and impacts of these participants, especially universities, often concentrate on low-vulnerability (LV) regions. There is a gap between the three major Mexican cities (Mexico City, Monterrey, and Guadalajara), where most of the actors concentrate, and the rest of the country [86]. Since most high-vulnerability (HV) regions lack a SEE supporting social ventures, some communities have created incipient local SEEs where a social or community-based enterprise is a central player that organizes and promotes the ecosystem [9].…”
Section: The Mexican Contextmentioning
confidence: 99%
“…On the other hand, research on social entrepreneurship and its financing is limited in Latin America [13]. As mentioned by Martínez and Dutrenit [14] in their report based on the UAM-Ashoka survey focused on Mexico, Latin America and the Caribbean, there are barriers or capabilities for social entrepreneurship to consolidate and maintain over time, where the main sources of financing come either from the contributions of partners or donations from third parties and, as a result, economic conditions are one of the main barriers to accessing financing, as well as the lack of public programs for social entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%